The role of integrated community case management projects in strengthening health systems: case study analysis in Ethiopia, Malawi and Mozambique - Story, William T; Pritchard, Susannah; Hejna, Emily; Olivas, Elijah; Sarriot, Eric (Health Policy and Planning, 2021)
Integrated community case management (iCCM) has now been implemented at scale globally. Literature to-date has focused primarily on the effectiveness of iCCM and the systems conditions required to sustain iCCM. In this study, we sought to explore opportunities taken and lost for strengthening health systems through successive iCCM programmes. We employed a systematic, embedded, multiple case study design for three countries—Ethiopia, Malawi and Mozambique—where Save the Children implemented iCCM programmes between 2009 and 2017. We used textual analysis to code 62 project documents on nine categories of functions of health systems using NVivo 11.0. The document review was supplemented by four key informant interviews. This study makes important contributions to the theoretical understanding of the role of projects in health systems strengthening by not only documenting evidence of systems strengthening in multi-year iCCM projects, but also emphasizing important deﬁciencies in systems strengthening efforts. Projects operated on a spectrum, ranging from gap-ﬁlling interventions, to support, to actual strengthening. While there were natural limits to the inﬂuence of a project on the health system, all successive projects found constructive opportunities to try to strengthen systems. Alignment with the Ministry of Health was not always static and simple, and ministries themselves have shown pluralism in their perspectives and orientations. We conclude that systems strengthening remains ‘everybody’s business’ and places demands for realism and transparency on government and the development architecture. While mid-size projects have limited decision space, there is value in better deﬁning where systems strengthening contributions can actually be made. Furthermore, systems strengthening is not solely about macro-level changes, as operational and efﬁciency gains at meso and micro levels can have value to the system. Claims of ‘systems strengthening’ are, however, bounded within the quality of evaluation and learning investments.
Keywords: G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; health / saúde

Estimating the cost of implementing a facility and community score card for maternal and newborn care service delivery in a rural district in Uganda - Ssebagereka, Anthony; Apolot, Rebecca Racheal; Nyachwo, Evelyne Baelvina; Ekirapa-Kiracho, Elizabeth (International Journal for Equity in Health, 2021)
This paper aimed at estimating the resources required to implement a community Score Card by a typical rural district health team in Uganda, as a mechanism for fostering accountability, utilization and quality of maternal and child healthcare service.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; community scorecard (CSC) / cartão de pontuação comunitária (CPC); gender / género; health - maternal and child / saúde - materno-infantil; health / saúde; youth / juventude

Democracy Index 2020 In sickness and in health? - The Economist Intelligence Unit (The Economist, 2020)
The main focus of the report is the impact of the coronavirus (Covid-19) pandemic on democracy and freedom around the world. It looks at how the pandemic resulted in the withdrawal of civil liberties on a massive scale and fuelled an existing trend of intolerance and censorship of dissenting opinion (see page 14). The report also examines the state of US democracy after a tumultuous year dominated by the coronavirus pandemic, the Black Lives Matter movement and a hotly contested presidential election (see page 42). The results by region are analysed in greater detail in the section entitled “Democracy around the regions in 2020” (see page 26).
Keywords: *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; civil society / sociedade civil; health - COVID-19 / saúde – COVID-19